3D printing geopolymer composite material with low drying shrinkage and preparation method thereof

By using components such as slag powder, fly ash, steel slag powder and quartz sand, combined with chemical agents such as sodium hydroxide, sodium silicate and barium chloride, low-dry shrinkage 3D printed geological polymer composites, the problems of too fast settling time and high drying shrinkage in the prior art are solved, and more stable compressive strength and lower carbon emissions are achieved.

CN119638286APending Publication Date: 2025-03-18HEBEI UNIV OF TECH

Patent Information

Application Number
CN202411807118.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, the alkali-excited poly gelled material system is difficult to construct when preparing 3D printed concrete.

Method used

Slag powder, fly ash, steel slag powder and quartz sand are used as main components, and alkali exciters are prepared by sodium hydroxide and sodium silicate, barium chloride is added as retarder, and the water-gluing ratio and stirring method are optimized to prepare low-drying shrinkage 3D printed geological polymer composite materials.

Benefits of technology

It significantly reduces carbon emissions and energy consumption, improves compressive strength and settling time, reduces drying shrinkage, and improves the performance and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638286A_ABST
    Figure CN119638286A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of 3D printing building materials, in particular to a 3D printing geopolymer composite material with low drying shrinkage and a preparation method thereof.The 3D printing geopolymer composite material is prepared from, by mass, 400 parts of slag powder, 320 parts of fly ash, 80 parts of steel slag micro powder, 1200 parts of quartz sand, 5.1-25.6 parts of sodium hydroxide, 46.4-66.9 parts of sodium silicate, 8 parts of barium chloride and 296 parts of water. The preparation method comprises the following steps: fully mixing the slag powder, the fly ash, the steel slag micro-powder and the quartz sand according to a preset mass ratio to obtain a uniform basic powder mixture; adding an alkali activator and barium chloride into the basic powder mixture, and continuously mixing until the mixture is uniform to obtain a first mixture; and adding water into the first mixture according to a preset water-binder ratio, and carrying out stirring treatment according to a preset stirring method to obtain the 3D printing geopolymer composite material with low drying shrinkage. According to the invention, the drying shrinkage can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of 3D printing building materials, and in particular to a 3D printing geopolymer composite material with low drying shrinkage and a preparation method thereof. Background Art

[0002] With the rapid development of intelligent construction technology, 3D printing concrete technology has become a hot topic for global research and application. With its significant advantages such as digital molding, moldless construction, material and labor savings, improved construction efficiency, and flexible and changeable shapes, this technology has shown a wide range of application potential. 3D printing concrete can not only reduce resource waste and environmental impact in traditional construction, but also provide innovative solutions for the precise manufacturing of complex structures, providing strong technical support for the efficient and green development of the future construction industry.

[0003] At present, cement-based materials are still one of the most commonly used materials in the field of 3D printing construction. However, the carbon emissions caused by the production of each ton of cement clinker are about 800 kg to 900 kg, which makes the production of cement one of the main sources of carbon emissions in the construction industry, causing significant pressure on the environment. Therefore, the use of green and low-carbon materials to reduce the carbon footprint of cement-based materials has become an important strategy to promote the transformation of 3D printing construction technology to green and sustainable development. In addition, the drying shrinkage problem of cement-based materials cannot be ignored. When the moisture inside the material is lost to the external environment, the loss of water in the pores and the decrease in relative humidity will lead to an increase in capillary pressure, thereby causing volume shrinkage and deformation. In contrast, alkali-activated geopolymer cementitious materials show great application potential. The material is composed of mineral components rich in aluminum, silicon, and calcium combined with an activator, which can significantly reduce carbon dioxide emissions and energy consumption during the production process. At the same time, this material system exhibits excellent mechanical properties, including high compressive strength and low drying shrinkage, providing new possibilities for the development of low-carbon and sustainable building materials.

[0004] At present, the technology of preparing 3D printed concrete using alkali-activated geopolymer cementitious material system has many defects. For example, the CN113105170A, CN114751768A, and CN113277791A cementitious material systems only consider improving the compressive strength, resulting in relatively high drying shrinkage and too fast setting time, making it difficult to construct.

[0005] Therefore, exploring whether it is possible to utilize industrial solid waste materials to develop a 3D printed geopolymer building material with low cost, low drying shrinkage, and stable strength is a key issue that needs to be urgently addressed in this field. Summary of the invention

[0006] To this end, the present invention provides a 3D printed geopolymer composite material with low drying shrinkage and a preparation method thereof, so as to overcome the problems of too fast setting time and relatively high drying shrinkage of 3D printed concrete prepared by an alkali-activated geopolymer cementitious material system in the prior art.

[0007] To achieve the above object, on the one hand, the present invention provides a 3D printing geopolymer composite material with low drying shrinkage, which is composed of the following components in parts by mass: 400 parts of slag powder, 320 parts of fly ash, 80 parts of steel slag powder, 1200 parts of quartz sand, 5.1 parts to 25.6 parts of sodium hydroxide, 46.4 parts to 66.9 parts of sodium silicate, 8 parts of barium chloride and 296 parts of water.

[0008] Furthermore, the CaO content in the slag powder is greater than 45%, the CaO content in the fly ash is greater than 10%, and the CaO content in the steel slag powder component is greater than 40%.

[0009] Furthermore, the particle size of the slag powder is 0.5 μm to 50 μm, the particle size of the fly ash is 0.5 μm to 200 μm, the particle size of the steel slag powder is 1 μm to 600 μm, and the particle size of the quartz sand is 208 μm to 415 μm.

[0010] Furthermore, the alkaline activator in the geopolymer composite material is a mixture of sodium silicate and sodium hydroxide; wherein, in terms of mass fraction, the sodium silicate is 46.4 to 66.9 parts, and the sodium hydroxide is 5.1 to 25.6 parts.

[0011] On the other hand, the present invention also provides a method for preparing a geopolymer composite material, comprising:

[0012] Step S1, fully mixing slag powder, fly ash, steel slag powder and quartz sand according to a preset mass ratio to obtain a uniform basic powder mixture;

[0013] Step S2, adding an alkali activator and barium chloride to the basic powder mixture, and continuing to mix until uniform, to obtain a first mixture; wherein the alkali activator includes sodium hydroxide and sodium silicate;

[0014] Step S3, adding water to the first mixture according to a preset water-binder ratio, and stirring the mixture according to a preset stirring method to obtain a 3D printing geopolymer composite material with low drying shrinkage.

[0015] Furthermore, in the step S1, it includes:

[0016] Step S11, obtaining the total CaO content in the slag powder, the fly ash and the steel slag powder, and determining the grinding pressure and the grinding speed according to the total CaO content;

[0017] Step S12, grinding the slag powder, the fly ash, the steel slag powder and the quartz sand based on the grinding pressure and the grinding speed;

[0018] Step S13, fully stirring and mixing the ground slag powder, fly ash, steel slag powder and quartz sand to obtain a uniform basic powder mixture.

[0019] Further, in the step S2, the base activator is obtained by the following method:

[0020] Sodium hydroxide is added to a preset mass of sodium silicate and mixed thoroughly to adjust the modulus of the sodium silicate to a preset modulus, thereby obtaining the alkali activator.

[0021] Further, in step S3, the preset stirring method includes:

[0022] The first mixture and water are stirred at a first stirring speed for a first stirring time to be preliminarily mixed, and then stirred at a second stirring speed for a second stirring time to be fully mixed into a uniform slurry, wherein the second stirring speed is greater than the first stirring speed.

[0023] Furthermore, in the step S2, the preset modulus is 0.6 to 1.0.

[0024] Furthermore, in the step S3, the second stirring speed is determined according to the fluidity of the first mixture after preliminary mixing with water.

[0025] Compared with the prior art, the beneficial effect of the present invention is that the components of the geopolymer composite material of the present invention adopt slag powder, fly ash, steel slag powder and quartz sand, which can realize the resource utilization of waste, reduce costs, and improve gelling properties and compressive strength. By using sodium hydroxide and sodium silicate to prepare an alkali activator for activation, carbon emissions and energy consumption can be significantly reduced, compressive strength can be improved, and drying shrinkage can be reduced. By adding barium chloride as a retarder, costs can be reduced, compressive strength can be further improved, and the performance and stability of the material can be improved.

[0026] Furthermore, the present invention can improve the uniformity of the basic powder mixture by fully mixing slag powder, fly ash, steel slag powder and quartz sand according to a preset mass ratio, thereby improving the efficiency and quality of subsequent alkali excitation, and using slag powder, fly ash and steel slag powder as raw materials can reduce costs. By adding alkali activator and barium chloride to the basic powder mixture for excitation, carbon emissions and energy consumption can be reduced, compressive strength can be improved, and drying shrinkage can be reduced. By adding water to the first mixture according to a preset water-binder ratio and stirring according to a preset stirring method, production efficiency and homogeneity can be improved, and compressive strength can be further improved.

[0027] Furthermore, the present invention uses sodium hydroxide to adjust the modulus of sodium silicate to a preset modulus to prepare an alkali activator, which can optimize the gelation process and pore structure and reduce drying shrinkage. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a flow chart of the method for preparing the geopolymer composite material according to an embodiment of the present invention;

[0029] Figure 2 Schematic diagram of the process of step S1 of the embodiment of the present invention;

[0030] Figure 3 This is a comparison diagram of the setting time of geopolymer composite materials under different preset moduli according to an embodiment of the present invention;

[0031] Figure 4 This is a comparison diagram of the compressive strength of the geopolymer composite material under different preset moduli after pouring for 7 days in the embodiment of the present invention;

[0032] Figure 5 This is a comparison diagram of the compressive strength of the geopolymer composite material after pouring for 28 days under different preset moduli in the embodiment of the present invention;

[0033] Figure 6 This is a comparison chart of the drying shrinkage of geopolymer composite materials under different preset moduli according to the embodiment of the present invention. DETAILED DESCRIPTION

[0034] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.

[0036] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.

[0037] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0038] The invention provides a 3D printing geopolymer composite material with low drying shrinkage. The geopolymer composite material consists of the following components in proportion by mass: 400 parts of slag powder, 320 parts of fly ash, 80 parts of steel slag powder, 1200 parts of quartz sand, 5.1 parts to 25.6 parts of sodium hydroxide, 46.4 parts to 66.9 parts of sodium silicate, 8 parts of barium chloride and 296 parts of water.

[0039] Specifically, the CaO content in the slag powder is greater than 45%, the CaO content in the fly ash is greater than 10%, and the CaO content in the steel slag powder component is greater than 40%.

[0040] Specifically, the particle size of the slag powder is 0.5 μm to 50 μm, the particle size of the fly ash is 0.5 μm to 200 μm, the particle size of the steel slag powder is 1 μm to 600 μm, and the particle size of the quartz sand is 208 μm to 415 μm.

[0041] Specifically, the alkaline activator in the geopolymer composite material is a mixture of sodium silicate and sodium hydroxide; wherein, in terms of mass fraction, the sodium silicate is 46.4 to 66.9 parts, and the sodium hydroxide is 5.1 to 25.6 parts.

[0042] The geopolymer composite material of the present invention is composed of slag powder, fly ash, steel slag powder and quartz sand, which can realize resource utilization of waste, reduce costs, and improve gelling performance and compressive strength. By using sodium hydroxide and sodium silicate to prepare an alkali activator for activation, carbon emissions and energy consumption can be significantly reduced, compressive strength can be improved, and drying shrinkage can be reduced. By adding barium chloride as a retarder, costs can be reduced, compressive strength can be further improved, and the performance and stability of the material can be improved.

[0043] See also Figure 1 As shown, it is a flow chart of the method for preparing a geopolymer composite material according to an embodiment of the present invention;

[0044] The present invention also provides a method for preparing a geopolymer composite material, comprising:

[0045] Step S1, fully mixing slag powder, fly ash, steel slag powder and quartz sand according to a preset mass ratio to obtain a uniform basic powder mixture;

[0046] It can be understood that the preset mass ratio is: 400 parts of slag powder, 320 parts of fly ash, 80 parts of steel slag powder, 1200 parts of quartz sand, 5.1 parts to 25.6 parts of sodium hydroxide, 46.4 parts to 66.9 parts of sodium silicate, 8 parts of barium chloride and 296 parts of water.

[0047] See also Figure 2 As shown, it is a flow chart of step S1 of an embodiment of the present invention; specifically, in step S1, it includes:

[0048] Step S11, obtaining the total CaO content in the slag powder, the fly ash and the steel slag powder, and determining the grinding pressure and the grinding speed according to the total CaO content;

[0049] It is understandable that the higher the total CaO content, the higher the degree of hardening of the slag powder, fly ash and steel slag powder, which will increase the flow resistance during grinding. It is necessary to increase the grinding pressure and grinding speed to fully grind the slag powder, fly ash and steel slag powder to achieve the best grinding effect.

[0050] In a specific embodiment, the total CaO content is the ratio of the sum of the mass of CaO in slag powder, the mass of CaO in fly ash and the mass of CaO in steel slag powder to the total mass of slag powder, fly ash and steel slag powder. The total CaO content is compared with a preset content. If the total CaO content is less than the preset content, the standard grinding pressure is determined as the grinding pressure, and the standard grinding speed is determined as the grinding speed. If the total CaO content is greater than or equal to the preset content, a first ratio is determined according to the ratio of the total CaO content to the preset content, the grinding pressure is determined according to the product of the first ratio and the standard grinding pressure, and the grinding speed is determined according to the product of the first ratio and the standard grinding speed.

[0051] It is understandable that the actual implementers can set the preset content according to the actual situation or based on the average of the total CaO content that has passed the qualification test in the historical data, and set the standard grinding pressure and the standard grinding speed according to the average of the grinding pressure and the average of the grinding speed corresponding to the preset content. Preferably, the preset content value range is set to 40% to 50%, the standard grinding pressure value range is set to 500kN to 600kN, and the standard grinding speed value range is set to 100r / min to 150r / min.

[0052] Step S12, grinding the slag powder, the fly ash, the steel slag powder and the quartz sand based on the grinding pressure and the grinding speed;

[0053] Step S13, fully stirring and mixing the ground slag powder, fly ash, steel slag powder and quartz sand to obtain a uniform basic powder mixture.

[0054] Step S2, adding an alkali activator and barium chloride to the basic powder mixture, and continuing to mix until uniform, to obtain a first mixture; wherein the alkali activator includes sodium hydroxide and sodium silicate;

[0055] In practice, barium chloride is added according to 1% of the total mass of the cementitious materials (slag powder, fly ash, steel slag powder).

[0056] See also Figure 3-Figure 6 As shown, Figure 3 This is a comparison diagram of the setting time of geopolymer composite materials under different preset moduli according to an embodiment of the present invention; Figure 4 This is a comparison diagram of the compressive strength of the geopolymer composite material under different preset moduli after curing for 7 days in an embodiment of the present invention; Figure 5 This is a comparison chart of the compressive strength of the geopolymer composite material under different preset moduli after curing for 28 days in an embodiment of the present invention; Figure 6 This is a comparison diagram of the drying shrinkage of geopolymer composite materials under different preset moduli in the embodiment of the present invention; in the figure, M06 represents a preset modulus of 0.6, M08 represents a preset modulus of 0.8, M10 represents a preset modulus of 1.0, and M12 represents a preset modulus of 1.2;

[0057] Specifically, in step S2, the base activator is obtained by the following method:

[0058] Sodium hydroxide is added to a preset mass of sodium silicate and mixed thoroughly to adjust the modulus of the sodium silicate to a preset modulus, thereby obtaining the alkali activator.

[0059] In practice, the preset mass is calculated by adding alkali activator according to 9% of the total mass of the cementitious materials (slag powder, fly ash, steel slag powder).

[0060] Specifically, in step S2, the preset modulus is 0.6-1.0, and preferably, the preset modulus is 0.6.

[0061] It can be understood that the modulus of sodium silicate is the molar ratio of silicon dioxide (SiO2) to sodium oxide (Na2O) in sodium silicate. Under low modulus (Ms = 0.6), the Na2O content in the sodium silicate solution is high, which significantly increases the concentration of Na+ in the system: Na2SiO3 + H2O → 2Na + +SiO3 2- , high concentration of Na + It will enhance the ionic strength of the solution, reduce the electrostatic repulsion between the silicon-oxygen polymer chains in the gel network through the ion shielding effect, and promote the formation of a dense and stable silicon-oxygen-aluminum skeleton structure. This dense gel structure helps to reduce porosity and reduce the water evaporation rate, thereby effectively controlling drying shrinkage. In addition, under low modulus conditions, Na + and OH - The high ion concentration accelerates the dissolution of active SiO2 and Al2O3 in fly ash, slag powder and steel slag powder: SiO2+2OH - →SiO3 2- +H2O,Al2O3+3OH - →2Al(OH) 4- This efficient dissolution and polycondensation reaction forms a uniformly distributed gel phase, and the internal pore structure is mainly composed of fine pores and micropores, which limits the migration path of water and significantly reduces the negative pressure effect and shrinkage stress accumulation caused by capillary action. In addition, under low modulus conditions, the high Na + The concentration increases the liquid viscosity, increases the water retention capacity of the slurry, and slows down the excessive evaporation of water during the drying process. Slow water migration reduces the accumulation of capillary pressure and reduces the stress concentration caused by drying shrinkage. At the same time, the dense gel network structure provides higher flexibility, which can moderately disperse the shrinkage stress and avoid the generation and expansion of microcracks. By adjusting the modulus of sodium silicate to 0.6 and using sodium hydroxide as an efficient stimulant, the present invention optimizes the chemical reaction process and pore structure design of geopolymer materials. The dense gel network and high water retention formed under low modulus conditions effectively inhibit the occurrence of volume shrinkage during the drying process, and significantly improve the dimensional stability and structural integrity of the cured material. This low drying shrinkage mechanism provides a more reliable performance guarantee for the engineering application of geopolymer materials.

[0062] The present invention uses sodium hydroxide to adjust the modulus of sodium silicate to a preset modulus to prepare an alkali activator, which can optimize the gelation process and pore structure and reduce drying shrinkage.

[0063] Step S3, adding water to the first mixture according to a preset water-binder ratio, and stirring the mixture according to a preset stirring method to obtain a 3D printing geopolymer composite material with low drying shrinkage.

[0064] Specifically, in step S3, the preset stirring method includes:

[0065] The first mixture and water are stirred at a first stirring speed for a first stirring time to be preliminarily mixed, and then stirred at a second stirring speed for a second stirring time to be fully mixed into a uniform slurry, wherein the second stirring speed is greater than the first stirring speed.

[0066] Specifically, in step S3, the second stirring speed is determined according to the fluidity of the first mixture after preliminary mixing with water.

[0067] In implementation, the preset water-cement ratio is 0.37, where the water-cement ratio is the ratio of the mass of water to the total mass of cementitious materials (slag powder, fly ash, and steel slag powder).

[0068] It is understandable that the smaller the fluidity of the first mixture after preliminary mixing with water, the worse the fluidity of the first mixture, and stratification or unevenness is more likely to occur during stirring, and it is necessary to improve the mixing uniformity of the materials by increasing the stirring speed.

[0069] In a specific embodiment, the fluidity of the first mixture after preliminary mixing with water (its average diameter expanded in the horizontal direction) is obtained to obtain the first fluidity, the first fluidity is compared with the preset fluidity, the second ratio is determined according to the ratio of the preset fluidity to the first fluidity, and the second stirring speed is determined according to the product of the second ratio and the first stirring speed. The second stirring speed can also be determined according to the difference between the preset fluidity and the first fluidity, as long as the second stirring speed is positively correlated with the difference between the first difference and the preset difference. The specific adjustment amount can be determined according to the actual scenario through several tests, which will not be repeated here. Preferably, the first stirring speed value range is set to 80r / min~90r / min, the preset fluidity value range is set to 200mm~220mm, the first stirring time value range is set to 2min~3min, and the second stirring time is set to 3min~4min.

[0070] In practice, the fluidity of 3D printed geopolymer composites can reach 250 mm to 280 mm.

[0071] The present invention can improve the uniformity of the basic powder mixture by fully mixing slag powder, fly ash, steel slag powder and quartz sand according to a preset mass ratio, thereby improving the efficiency and quality of subsequent alkali excitation, and using slag powder, fly ash and steel slag powder as raw materials can reduce costs. By adding alkali activator and barium chloride to the basic powder mixture for excitation, carbon emissions and energy consumption can be reduced, compressive strength can be improved, and drying shrinkage can be reduced. By adding water to the first mixture according to a preset water-binder ratio and stirring according to a preset stirring method, production efficiency and homogeneity can be improved, and compressive strength can be further improved.

[0072] Comparative Example:

[0073] The comparative example includes the following components by mass: 400 parts of slag powder, 320 parts of fly ash, 80 parts of steel slag powder, 1200 parts of quartz sand, 0 parts of solid flaky sodium hydroxide, 72 parts of solid granular sodium silicate, 8 parts of barium chloride, and 296 parts of water. The comparative example geopolymer composite material is prepared by the preparation method of the geopolymer composite material of the present invention. The obtained comparative example geopolymer composite material is poured into a 40mm×40mm×40mm test mold and flattened, and vibrated on a high-frequency vibration table for 40 to 60s. After the vibration is completed, the surface of the test piece is covered with a plastic wrap, and the test piece is demoulded after standing indoors for 2d; after demoulding, the test piece is placed in a standard curing box with a temperature of 20±2°C and a humidity of ≥95% for curing for 28d, during which the initial setting time is 45min and the final setting time is 70min; then, according to relevant standards, relevant performance tests are carried out, and the compressive strength performance test results of the comparative example are shown in Table 1, and the drying shrinkage performance test results of the comparative example are shown in Table 5.

[0074] Embodiment 1:

[0075] This embodiment includes the following components by mass: 400 parts of slag powder, 320 parts of fly ash, 80 parts of steel slag powder, 1200 parts of quartz sand, 5.1 parts of solid flaky sodium hydroxide, 66.9 parts of solid granular sodium silicate, 8 parts of barium chloride, and 296 parts of water. The geopolymer composite material preparation method of the present invention is used for preparation. The obtained geopolymer composite material of Example 1 is poured into a 40mm×40mm×40mm test mold and scraped flat, and vibrated on a high-frequency vibration table for 40 to 60s. After the vibration is completed, the surface of the test piece is covered with a plastic wrap, and the test piece is demoulded after standing indoors for 2d; after demoulding, the test piece is placed in a standard curing box with a temperature of 20±2°C and a humidity of ≥95% for curing for 28d, during which the initial setting time is detected to be 85min and the final setting time is 125min; then, according to relevant standards, relevant performance tests are carried out, and the compressive strength performance test results of Example 1 are shown in Table 2, and the drying shrinkage performance test results of Example 1 are shown in Table 5.

[0076] Embodiment 2:

[0077] This embodiment includes the following components by mass: 400 parts of slag powder, 320 parts of fly ash, 80 parts of steel slag powder, 1200 parts of quartz sand, 15.3 parts of solid flaky sodium hydroxide, 56.7 parts of solid granular sodium silicate, 8 parts of barium chloride, and 296 parts of water. The geopolymer composite material preparation method of the present invention is used for preparation. The obtained geopolymer composite material of Example 2 is poured into a 40mm×40mm×40mm test mold and scraped flat, and vibrated on a high-frequency vibration table for 40 to 60s. After the vibration is completed, the surface of the test piece is covered with a plastic wrap, and the test piece is demolded after standing indoors for 2d; after demolding, the test piece is placed in a standard curing box with a temperature of 20±2°C and a humidity of ≥95% for curing for 28d, during which the initial setting time is 100min and the final setting time is 135min; then, according to relevant standards, relevant performance tests are carried out, and the compressive strength performance test results of Example 2 are shown in Table 3, and the drying shrinkage performance test results of Example 2 are shown in Table 5.

[0078] Embodiment 3:

[0079] This embodiment includes the following components by mass: 400 parts of slag powder, 320 parts of fly ash, 80 parts of steel slag powder, 1200 parts of quartz sand, 25.6 parts of solid flaky sodium hydroxide, 46.4 parts of solid granular sodium silicate, 8 parts of barium chloride, and 296 parts of water. The geopolymer composite material preparation method of the present invention is used for preparation. The obtained geopolymer composite material of Example 3 is poured into a 40mm×40mm×40mm test mold and scraped flat, and vibrated on a high-frequency vibration table for 40 to 60s. After the vibration is completed, the surface of the test piece is covered with a preservative film, and the test piece is demolded after standing indoors for 2d; after demolding, the test piece is placed in a standard curing box with a temperature of 20±2°C and a humidity of ≥95% for curing for 28d, during which the initial setting time is 125min and the final setting time is 155min; then, according to relevant standards, relevant performance tests are carried out, and the compressive strength performance test results of Example 3 are shown in Table 4, and the drying shrinkage performance test results of Example 3 are shown in Table 5.

[0080] Part of the raw materials used in the above examples and comparative examples are specifically:

[0081] The slag used was slag powder obtained from Baifeng Mineral Products Processing Plant in Lingshou County, Hebei Province. It was white in color and had a CaO content of 47.1%.

[0082] The steel slag used is steel slag powder produced by Taizhen Mineral Products Processing Plant in Lingshou County, Hebei Province. It is gray-black in color and has a CaO content of 41.6%.

[0083] The slag used is the first-grade fly ash produced by Aohong Mineral Products Management Department in Lingshou County, Hebei Province, with a gray-brown color and a CaO content of 12.8%;

[0084] Sodium silicate and sodium hydroxide are used as alkaline activators, wherein sodium silicate (Na2SiO3) is provided by Lusen Chemical Co., Ltd., Linyi City, Shandong Province, and the modulus of anhydrous sodium silicate (M=n(SiO2) / n(Na2O)) is approximately equal to 1.2. Sodium hydroxide (NaOH) is provided by Yatai United Chemical Co., Ltd., Wuxi City, Jiangsu Province, and the purity is greater than 99.9%.

[0085] The test methods and standards for each specimen are as follows:

[0086] The setting time of 3D printed geopolymer concrete materials was tested according to the provisions of the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009);

[0087] According to the "Test Method for Cement Mortar Strength" (GB / T17671-1999), the compressive strength of the specimens was tested using a high-precision universal testing machine.

[0088] According to the provisions of "Determination of fluidity of cement mortar" (GB / T2419-2005), an electric jumping table test is carried out to check whether it meets the fluidity test standards for 3D printing.

[0089] Table 1 Comparative Example Compressive Strength Performance Test Results

[0090]

[0091]

[0092] Table 2 Compressive strength performance test results of Example 1

[0093]

[0094] Table 3 Compressive strength performance test results of Example 2

[0095]

[0096]

[0097] Table 4 Compressive strength performance test results of Example 3

[0098]

[0099] Table 5 Drying shrinkage performance test results

[0100]

[0101]

[0102] The contents in the above table show that the compressive strength of the 3D printed geopolymer composite material with low drying shrinkage prepared by the components and proportions of the present invention is relatively stable, the setting time is improved, and the drying shrinkage rate is significantly reduced, and the geopolymer composite material prepared by the preset modulus of 0.6 corresponding to the alkali activator has the lowest drying shrinkage rate.

[0103] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.

Claims

1. A 3D printed geopolymer composite material with low drying shrinkage, characterized in that: The geopolymer composite material is composed of the following components in parts by mass: 400 parts of slag powder, 320 parts of fly ash, 80 parts of steel slag powder, 1200 parts of quartz sand, 5.1 parts to 25.6 parts of sodium hydroxide, 46.4 parts to 66.9 parts of sodium silicate, 8 parts of barium chloride and 296 parts of water.

2. The 3D printing geopolymer composite material with low drying shrinkage according to claim 1, characterized in that: The CaO content in the slag powder is greater than 45%, the CaO content in the fly ash is greater than 10%, and the CaO content in the steel slag powder component is greater than 40%.

3. The 3D printed geopolymer composite material with low drying shrinkage according to claim 2, characterized in that: The particle size of the slag powder is 0.5 μm to 50 μm, the particle size of the fly ash is 0.5 μm to 200 μm, the particle size of the steel slag powder is 1 μm to 600 μm, and the particle size of the quartz sand is 208 μm to 415 μm.

4. The 3D printed geopolymer composite material with low drying shrinkage according to claim 3, characterized in that: The alkaline activator in the geopolymer composite material is a mixture of sodium silicate and sodium hydroxide; wherein, in terms of mass fraction, the sodium silicate is 46.4 to 66.9 parts, and the sodium hydroxide is 5.1 to 25.6 parts.

5. A method for preparing a geopolymer composite material, which is used to prepare a 3D printing geopolymer composite material with low drying shrinkage as described in any one of claims 1 to 4, characterized in that: include: Step S1, fully mixing slag powder, fly ash, steel slag powder and quartz sand according to a preset mass ratio to obtain a uniform basic powder mixture; Step S2, adding an alkali activator and barium chloride to the basic powder mixture, and continuing to mix until uniform, to obtain a first mixture; wherein the alkali activator includes sodium hydroxide and sodium silicate; Step S3, adding water to the first mixture according to a preset water-binder ratio, and stirring the mixture according to a preset stirring method to obtain a 3D printing geopolymer composite material with low drying shrinkage.

6. The method for preparing a geopolymer composite material according to claim 5, characterized in that: In the step S1, it includes: Step S11, obtaining the total CaO content in the slag powder, the fly ash and the steel slag powder, and determining the grinding pressure and the grinding speed according to the total CaO content; Step S12, grinding the slag powder, the fly ash, the steel slag powder and the quartz sand based on the grinding pressure and the grinding speed; Step S13, fully stirring and mixing the ground slag powder, fly ash, steel slag powder and quartz sand to obtain a uniform basic powder mixture.

7. The method for preparing a geopolymer composite material according to claim 6, characterized in that: In the step S2, the base activator is obtained by the following method: Sodium hydroxide is added to a preset mass of sodium silicate and mixed thoroughly to adjust the modulus of the sodium silicate to a preset modulus, thereby obtaining the alkali activator.

8. The method for preparing a geopolymer composite material according to claim 7, characterized in that: In step S3, the preset stirring method includes: The first mixture and water are stirred at a first stirring speed for a first stirring time to be preliminarily mixed, and then stirred at a second stirring speed for a second stirring time to be fully mixed into a uniform slurry, wherein the second stirring speed is greater than the first stirring speed.

9. The method for preparing a geopolymer composite material according to claim 8, characterized in that: In the step S2, the preset modulus is 0.6-1.

0.

10. The method for preparing a geopolymer composite material according to claim 9, characterized in that: In the step S3, the second stirring speed is determined according to the fluidity of the first mixture after preliminary mixing with water.

Citation Information

Patent Citations

  • 3D printing alkali-activated geopolymer composite material doped with hibiscus cannabinus bast fiber crop straw, and preparation method thereof

    CN113105170A

  • Industrial solid waste geopolymer material for building 3D printing and preparation method thereof

    CN113277791A

  • Lightweight high-strength recycled aggregate geopolymer mortar for 3D printing and preparation method of lightweight high-strength recycled aggregate geopolymer mortar

    CN114751768A

Cited By

  • Geopolymer material for mine hole plugging and preparation method thereof

    CN120441218A

  • A geopolymer material for mine tunnel sealing and preparation method thereof

    CN120441218B